Efectos pleotrópicos de inhibidores de 3-hidroxi-3-metilglutaril-coa reductasa en nefropatía obstructiva - Kurbán Carosella, Fernando Tufik (2009)
The incidence of chronic renal diseases is increasing world-wide, and there is a great need to identify therapies capable of arresting or reducing disease progression. The current treatment of chronic nephropathies is limited to angiotensin-converting enzyme inhibitors and angiotensin receptor blockers, but there is growing clinical and experimental evidence that statins (3-hydroxy-3-methyglutaryl-CoA reductase inhibitors) could play a therapeutic role.